A case of latanoprost‐induced diffuse facial skin hyperpigmentation. (28th March 2019) - Kim, Ho Young; Lee, Soo Kyung; Lee, Jae Ho; Suh, Joong Heon; Kim, Myoung Shin; Lee, Un Ha
Summary: Introduction: Latanoprost is a prostaglandin F2α analogue, which has been used as a first‐line drug for open‐angle glaucoma. Common side effects of latanoprost include hyperpigmentation. While it usually occurs on irides or periocular skin, diffuse facial hyperpigmentation is rarely reported. Case presentation: A 71‐year‐old woman was presented with diffuse gray‐brown colored maculopatches on her face. The symptom appeared 1 week after she started to use latanoprost eye drops for glaucoma. Biopsy specimen revealed vacuolar degeneration of dermo‐epidermal junction and pigment incontinence in dermis. Objective: The aim of this paper is to introduce a rare adverse effect of latanoprost and effective way of treatment. Methods: We stopped her from using latanoprost. She was also treated with 532‐nm potassium titanyl phosphate laser and low‐fluence 1064‐nm Q‐switched Nd:YAG laser, while using topical agents. Result: After 10 weeks, we observed hyperpigmentation of her face was effectively and safely treated. The patient was satisfied with the result. Conclusion: Diffuse facial pigmentation could be one of the latanoprost‐induced adverse effects and the laser treatments with topical agents we used can make it improve faster.